OBEMIRISK‐Knowledge platform for assessing the risk of bisphenols on gut microbiota and its role in obesogenic phenotype: looking for biomarkers. Issue 4 (29th April 2022) - Aguilera, Margarita; López‐Moreno, Ana; Cerk, Klara; Suárez, Antonio; Houdeau, Eric; Lamas, Bruno; Cartier, Christel; Gaultier, Eric; Zalko, Daniel; Van Pamel, Els; Heyndrickx, Marc; Rasschaert, Geertrui; et al.
Abstract: "Obemirisk – Knowledge platform for assessing the risk of Bisphenols on gut microbiota and its role in obesogenic phenotype: looking for biomarkers" was a knowledge transfer project funded by the European Food Safety Authority (EFSA) that integrated a multidisciplinary team from Spain, France, Belgium, Slovakia and Poland. This project aimed to strengthen the knowledge capacity to assess the risk of bisphenol A and several structural analogues on gut microbiota that could mediate the obesogenic phenotype in childhood. Protocols and methodologies from different fields such as chemical analysis (food and biosamples), nutrition (surveys and questionnaires), microbiology (culturomics and metagenomics), and gene reporter assay (AhR‐Ligand) have been applied and shared. Several data generated under the project are available under open publications and databases for the Consortium and scientific community. Common documents and publications integrating data from endocrine disrupting chemicals (EDCs), bisphenols, microbiota dysbiosis and obesity were elaborated. A networking and specific capacity‐building programmes have been implemented to produce and share the new data on bisphenols data food composition, microbiota and its impact on obesity between providers and recipients' partners. Scientific exchanges and specific designed courses provided training for students in the risk characterization related domains. The project was mainly focused on the bisphenols´ presence in consumed foods by Spanish children and in several children biosamples (saliva, urine, nails, and hair). Moreover, a pilot project on obese vs . normal‐weight children allowed to determine the obesity‐linked microbiota dysbiosis through metagenomics and specific biomarkers of the dysregulated microbiota‐immune system axis (AhR‐Ligands). The Obemirisk project applied a collaborative and multidisciplinary approach to establish scientific data compilation for harmonising risk assessment and to perform trainings on next generation of risk assessment where microbiome disruption might become a robust biomarker to be used in food safety. Several aspects of the process of capacity building have been mainly conceptual due to the COVId‐19 pandemic and will be further implemented through presential exchanges. Moreover, the consortium work strategy can also propose further EU collaborations for refining and elucidating the impact and mechanisms of bisphenols altering human microbiomes and triggering obesity. The knowledge, analyses and the integrative approach will be extrapolated for other foods, age ranges, geographical areas, and other biomatrices. For grant agreements: © OBEMIRISK consortium, 2022